Transient study of the oxygen reduction reaction on reduced Pt and Pt alloys microelectrodes: evidence for the reduction of pre-adsorbed oxygen species linked to dissolved oxygen. Issue 44 (23rd October 2015) - Perry, S. C.; Denuault, G.
Abstract : Below 100 ms the reduction of oxygen on oxide-free Pt microdisc electrodes reveals the existence of oxygen species which adsorb on the electrode before the reduction is electrochemically driven. Abstract : Using chronoamperometry at preconditioned oxide-free Pt microdisc electrodes in aqueous media, we investigated the oxygen reduction reaction (ORR) on the millisecond timescale and obtained results consistent with the reduction of oxygen species which adsorb on the electrode before the ORR is electrochemically driven. Furthermore these adsorbed species are clearly linked to oxygen in solution. At long times, the amperometric response is solely controlled by the diffusion of dissolved oxygen towards the microelectrode. However, at short times, typically below 50 ms, the reduction of pre-adsorbed oxygen produces a large extra current whose magnitude depends on the oxygen concentration in solution, deliberate electrode poisoning and the rest time before the potential step. Using sampled current voltammetry we show that this extra current affects the entire potential range of the ORR. Using microdisc electrodes made with Pt alloys we find that the amperometric response is sufficiently sensitive to distinguish oxygen coverage differences between Pt, Pt0.9 Rh0.1 and Pt0.9 Ir0.1 microdiscs. These unexpected and, to our knowledge, never previously reported results provide new insight into the oxygen reduction reaction on Pt. The existence over a wide potential range of irreversibly adsorbed oxygen species arising from dissolved oxygen and different from Pt oxide is particularly relevant to the development of oxygen reduction catalysts for low temperature fuel cells.